Bioinformatics-guided decoding of the Ancylostoma duodenale genome for the identification of potential vaccine targets - Mohibullah Shah; Hira Anum; Asifa Sarfraz; Md. Aktaruzzaman; Al Riyad Hasan; Muhammad Umer Khan; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. N. Alasmari; Abid Ali; Umar Nishan; Ke Chen (BMC Genomics)
Abstract Ancylostoma duodenale, a parasitic nematode worm, is found to be involved in various infections, including intestinal blood loss, protein malnutrition, and anemia. Antimicrobial resistance to the available therapeutics has prompted the search for new drug and vaccine targets against A. duodenale. Despite significant advances in vaccine development against A. duodenale, no commercial and FDA-approved vaccine exists to safeguard humans from infections caused by this pathogen. In this investigation, a stringent bioinformatics analysis identified 36 unique essential and host-interacting proteins. Based on their subcellular localization, 6 proteins located in the extracellular space and outer membrane were categorized as vaccine targets, while the remaining proteins were predicted to act as potential drug candidates. These vaccine candidates were further assessed for antigenicity, allergenicity, and physicochemical analysis to determine their suitability for the designing of a multi-epitope vaccine. Two candidate proteins were chosen as optimal targets in the development of vaccine design. The identified T- and B-cell epitopes from these proteins were then combined with appropriate linkers and adjuvants to design chimeric vaccine constructs aimed at inducing both cellular and humoral immune responses. Molecular docking, molecular dynamic simulations, PCA analysis, DCCM analysis, and binding free energy calculations proved stable interactions of the designed vaccine with human immune cell receptors. Within a bacterial cloning system, the vaccine constructs demonstrated the ability to be cloned and expressed. The immunological stimulation elicited significant immunological responses to the proposed vaccine. Our investigation identified new therapeutic targets and developed a peptide-based multi-epitope vaccine against A. duodenale infection. Additional experimental verification will open up new therapeutic alternatives for this emerging resistant pathogen.